PENGARUH PSIKOEDUKASI KELUARGA TERHADAP PERUBAHAN TINGKAT KECEMASAN DAN PERSEPSI BEBAN KELUARGA MERAWAT ANAK DENGAN RETARDASI MENTALDI SDLB NEGERI KABUPATEN JOMBANG - Lilik Supriati**, Shanti Rosmaharani* Titin Andri Wihastuti** (Universitas Muhammadiyah Jember, 2015)
Families with mental retardation have a higher tendency of psychosocial problems. The problems is ussually caused by children disability and high level of dependency to their parents. Anxiety and the perception of burden are problems that often arise when caring children with mentak retardation. The purpose of this study was to determine the influence of family psychoeducation to the level of anxiety and the perception of family burden in caring of children with mental retardation. The study design was quasy experimental pre-post test with control group. The purposive sampling tchnique was used to obtain 12 samples of treatment group and 12 samples for control group. Data obataine pre and post family psychoeducation, then compared to control group. Result showed the change in the treatmentgroup which are the decrease of anxiety levels with p value (0.03) and perceptions of family burden with p value (0.04) is less than ? (0.05). family psychoeducation is recommended to adress psychosocial problems in the family wahich are anxiety and perception of family burden